Legal Protection for Sharia Bank Customers in the Digital Era Following the Issuance of Law Number 4 of 2023 Concerning the Development and Strengthening of the Financial Sector - Nurhasanah Br Sinulingga; Ahmad Wahyudi Zein (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study examines the legal protection available to customers of Islamic banking in Indonesia within the framework of national banking regulations. The purpose of the research is to identify how the law safeguards the rights and interests of Islamic bank customers, considering that such protection is essential not only for conventional banking customers but also for all financial institutions. The urgency of this topic arises from the fact that Islamic banking is relatively new in Indonesia, making it more susceptible to various challenges and disputes in practice that may potentially harm customers as the main consumers of banking services. The research adopts a normative juridical approach, emphasizing an analysis of legal norms, principles, and rules that regulate banking activities in Indonesia. The data sources consist of primary legal materials, including laws and regulations governing banking, and secondary legal materials, such as academic literature, journals, and other relevant documents. Data collection is conducted through a library research method, while data analysis employs a descriptive-analytical technique to systematically describe, explain, and assess the legal framework in order to provide a clear understanding of the extent of legal protection for Islamic banking customers.